Rapid Universal Neonatal Hearing Screening (UNHS) using a fast Automated Auditory Brainstem Response (AABR) - Bradley, Andrew; Wilson, Wayne; Petoe, Matthew; Dzulkarnain, Ahmad Aidil Arafat (2008)
Universal Newborn Hearing Screening (UNHS) is an important tool for detecting hearing impairment in newborns, but it is often hindered by unacceptably long test times. The successful reduction of these test times would be of significant benefit to both the institutions and the societies providing UNHS services. 144 neonates were assessed using a new automated auditory brainstem response (AABR) test that combines new maximum length sequence (MLS) techniques with automated analysis techniques. Initial analyses of this data suggest this new AABR test has the potential to reduce average screening times per newborn from minutes to seconds, with some limitations. Discussion: The implications of this data and the plans for future research will be discussed